2015
DOI: 10.5902/2179460x17309
|View full text |Cite
|
Sign up to set email alerts
|

Aspectos Morfológicos E Fisiológicos Da Germinação E Morfometria De Frutos E Sementes De Swartzia Recurva Poeep (Fabaceae)

Abstract: Objetivou-se fornecer dados da morfometria de frutos e sementes, germinação e do desenvolvimento pós-seminal de Swartzia recurva. Foram avaliados: massa fresca, comprimento, largura e espessura dos frutos/sementes. Quanto à forma, coloração e textura do pericarpo e nas sementes observou-se: forma, coloração, textura e presença de projeções carnosas descreveu a. emergência, tipo de morfologia da plântula, hipocótilo e epicótilo, cotilédone e eofilos. O teste de germinação foi conduzido na luz e escuro contínuo,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
0
2
0
4
Order By: Relevance
“…Researches conducted with fruit and seeds of species from different botanical families such as majestic heaven lotus (Gustavia augusta L., Lecythidaceae Family) by Silva et al (2014), cucumber tree (Averrhoa bilimbi L., Oxalidaceae Family) by Santos et al (2015), and Campomanesia adamantium (Myrtaceae Family) by Dresch et al (2013), indicated that longer and wider fruits presented higher values of fruit mass and seeds. Similar results were obtained in the present study, where the three rootstocks presenting higher values of fruit mass (Table 1) were also the ones presenting seeds with bigger dimension and seed fresh mass (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Researches conducted with fruit and seeds of species from different botanical families such as majestic heaven lotus (Gustavia augusta L., Lecythidaceae Family) by Silva et al (2014), cucumber tree (Averrhoa bilimbi L., Oxalidaceae Family) by Santos et al (2015), and Campomanesia adamantium (Myrtaceae Family) by Dresch et al (2013), indicated that longer and wider fruits presented higher values of fruit mass and seeds. Similar results were obtained in the present study, where the three rootstocks presenting higher values of fruit mass (Table 1) were also the ones presenting seeds with bigger dimension and seed fresh mass (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Many research works conducted with fruits and seeds of tree species from different botanical families, such as cucumber tree (Averrhoa bilimbi L.) of Oxalidaceae family [33], Campomanesia adamantium of Myrtaceae family [34], and majestic heaven lotus (Gustavia augusta L.) from Lecythidaceae family [35], indicate that longer and wider fruits usually present higher values of fruit mass and seeds. These authors' results are in total agreement with the results of our study which showed that longer, wider, and heavier fruits have more seeds.…”
Section: Fruit Lengthmentioning
confidence: 99%
“…A expansão dos cotilédones foliáceos/fotossintéticos, na maioria das espécies, ocorre apenas após a germinação (Cosmo et al, 2017), pois estes são considerados uma adaptação para explorar aumentos na disponibilidade luminosa por meio de áreas abertas da floresta (Santos et al, 2015).…”
Section: Discussionunclassified
“…Em contrapartida, os cotilédones de reserva são considerados uma adaptação que confere às plântulas em ambientes sombreados, um maior tempo de sobrevivência, pois eles fornecem uma reserva nutricional capaz de conferir a energia necessária até o surgimento condições favoráveis. Além disso, possuem a capacidade de germinar em maiores profundidades (Santos et al, 2015), existindo, assim, a possibilidade de fazer uma classificação das espécies com relação ao grupo funcional ao qual elas pertencem.…”
Section: Discussionunclassified